1983
DOI: 10.1017/s0021859600033451
|View full text |Cite
|
Sign up to set email alerts
|

Thermal adjustments of steers (Bos taurus) to abrupt changes in environmental temperature

Abstract: Body heat storage changes of cattle were measured by means of simultaneous direct and indirect calorimetry and by thermometry in an environment that alternated in temperature between 12 and 25 °C. When the calorimeter temperature was increased deep body temperature (T c ) increased by approximately 0-5 °C, mean surface temperature (T t ) by 3 °C and mean body temperature (determined from calorimetry, T s ) by 1 °C, but these increases were not fully sustained during the next 24 h. Changes in the three temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 10 publications
2
15
1
Order By: Relevance
“…1) resembles results reported by Slee and Sykes (1967) and Slee (1972) in sheep. In contrast, McLean et al (1983a) observed that carotid artery temperature of three Ayrshire steers declined very slowly when ambient temperature was suddenly reduced from 25 to 12°C. Hahn and Mader (1997) reported that diurnal body temperature rhythms lag behind ambient conditions by 3 to 5 h under heat stress conditions, and 8 to 10 h in moderate conditions.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…1) resembles results reported by Slee and Sykes (1967) and Slee (1972) in sheep. In contrast, McLean et al (1983a) observed that carotid artery temperature of three Ayrshire steers declined very slowly when ambient temperature was suddenly reduced from 25 to 12°C. Hahn and Mader (1997) reported that diurnal body temperature rhythms lag behind ambient conditions by 3 to 5 h under heat stress conditions, and 8 to 10 h in moderate conditions.…”
Section: Discussionmentioning
confidence: 74%
“…Results of the present study suggest that beef cattle, like sheep, respond very quickly to the sudden onset of severe cold exposure. The nature of this response was much more rapid and the reverse of that observed by McLean et al (1983a) at more moderate temperatures in a gradually cooling environment.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Amongst farm animals, those which allow a greater variation in body heat storage could in theory have an advantage in terms of food conversion efficiency (McLean et al 1983a). …”
Section: Feed Intakementioning
confidence: 99%